An International Examination of the Effectiveness of Functional Family Therapy (FFT) in a Danish Community Sample. (13th September 2019) - Vardanian, Maria Michelle; Scavenius, Christoffer; Granski, Megan; Chacko, Anil
Abstract : Youth behavior problems have increased in prevalence in Scandinavian countries. Functional Family Therapy (FFT) has been shown to be an effective intervention across diverse populations and international contexts. The current study examines the effectiveness of FFT within a Danish‐community sample in a pre‐post comparison design and includes 687 families. Observed outcomes included both parent‐ and/or youth‐ reported domains of youth behavior, family dysfunction, school attendance and performance, and substance use. Significant improvements were found in youth behavior, family functioning, and school‐related outcomes (e.g., like of school and truancy) despite experiencing a 60% attrition rate in our sample postintervention. This study provides evidence for the effectiveness of FFT on a wide scale in a Scandinavian context, adding to previous research that supports the transportability of this intervention.